2020
DOI: 10.9734/ajaar/2020/v14i430137
|View full text |Cite
|
Sign up to set email alerts
|

Straw, Seed Yield and Quality of Three Linum usitatissimum L. Cultivars in Relation to Nitrogen Fertilizer Rate and Plant Density

Abstract: Methodology: Two field experiments were conducted on the Experimental Farm at El-Gemmeiza Research Station, Gharbia Governorate, Agricultural Research Center, Egypt, during two successive winter seasons of 2018-19 and 2019-20. Aims: To investigate the effect of three nitrogen fertilizer rates, i.e. 30, 50 and 70 kg N feddan-1 [one feddan (fed) = 4200 m2] and three plant densities, i.e. 1500, 2000 and 2500 seeds m-2 on flax (Linum usitatissimum L.) yield and its quality of three cultivars of flax, i.e. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The reason for the superiority of the Back Coat variety may be due to the nature of this genotype, its response to environmental conditions, its increased vegetative growth, cell division, and the activity of vital processes. These results are consistent with the findings of [25,26], who found that the varieties differed significantly in the number of secondary branches in the plant. The cotton plants that were sprayed with a concentration of 150 mg L -1 of melatonin performed exceptionally well, with a mean for the trait of 3.95 branches per plant -1 , a 60% increase from the control plants, which produced the lowest mean of 2.46 branches per plant-1.…”
Section: The Number Of Vegetative Branches In the Plant (Branch Plant...supporting
confidence: 92%
“…The reason for the superiority of the Back Coat variety may be due to the nature of this genotype, its response to environmental conditions, its increased vegetative growth, cell division, and the activity of vital processes. These results are consistent with the findings of [25,26], who found that the varieties differed significantly in the number of secondary branches in the plant. The cotton plants that were sprayed with a concentration of 150 mg L -1 of melatonin performed exceptionally well, with a mean for the trait of 3.95 branches per plant -1 , a 60% increase from the control plants, which produced the lowest mean of 2.46 branches per plant-1.…”
Section: The Number Of Vegetative Branches In the Plant (Branch Plant...supporting
confidence: 92%
“…The reason for the superiority of the Coker 310 cultivar may lie in the nature of this cultivar and its response to environmental conditions (temperature and photoperiod), resulting in increased vegetative growth and metabolic activity. This aligns with Gedwy et al, [21] and Omar [22], which indicated that cultivars differ significantly in number of vegetative branches per plant. Additionally, significant differences were observed among boron concentrations, with the concentration of 120 mg L -1 recording the highest mean at 3.54 vegetative branches plant -1 compared to the control treatment, which gave a lower mean of 3.13 vegetative branches plant -1 .…”
Section: Number Of Vegetative Branches Plant -1supporting
confidence: 91%
“…The reason for this superiority may be attributed to the nature of the Coker 310 cultivar and its response to environmental conditions (temperature and photoperiod). These results align with Al-Fahdawi et al, [25], Naqeeb et al, [26], Gedwy et al, [21], and Omar [22], which indicated that cultivars differ significantly in the trait of the number of fruiting branches per plant. Also, there were noticeable variations between the different boron concentrations; for example, the control treatment yielded a mean of 10.85 branches per plant, while the dosage of 120 mg L -1 produced the highest mean of 13.76 branches per plant.…”
Section: Number Of Fruiting Branches Per Plantsupporting
confidence: 91%
“…Plant height and technical length increased with the increase in plant density and reached up to 1750 plant m −2 plant density, but decreased again at 2000 plant m −2 plant density. According to research on flax sowing density, 2250 plant m −2 was suggested for the highest plant height and technical length [28] and 2500 seeds m −2 [33]. This was also observed by researchers [34,35] recommended 1800 plants m −2 density.…”
Section: Discussionmentioning
confidence: 55%
“…Flax planting density varied according to climatic conditions. For example, Lithuanian circumstances, 2200-2500 plants m −2 have been recommended [46], while the maximum fiber yield was recorded at 2500 plant m −2 , and the lowest fiber yield was noticed at 1500 plant m −2 , and 2500 plant m −2 was recommended for high straw yield, fiber yield, seed yield and technical length [33]. However, [28] it is suggested that the seeding rate of 2250 seed m −2 for straw yield and its components viz, plant height, technical length, number of higher branches plant −1 , stem diameter and straw yield plant −1 .…”
Section: Discussionmentioning
confidence: 99%